Exploring the link between physicians' caffeine use disorders with sleep quality and professional burnout: a cross-sectional study - Büşra Sağlam; Egemen Tural; Akın Dayan (BMC, 2024)
Abstract Background The objective of this research was to examine how caffeine use disorder among physicians across different specialties relates to both sleep quality and professional burnout. Methods This research represents a single-center, prospective, cross-sectional study involving 240 physicians meeting inclusion criteria and working within a training and research hospital. Participants were enrolled in the study after obtaining informed consent. A web-based survey methodology was employed, administering a participant information form crafted following an exhaustive literature review, alongside assessments utilizing the Caffeine Use Disorder Questionnaire, the Pittsburgh Sleep Quality Index, and the Maslach Burnout Inventory. A significance level of p < 0.05 was considered statistically significant. Results In our study, participants had a median age of 30.0 years, and 60% reported poor sleep quality. A positive and statistically significant relationship (rho=0.148, p = 0.022) was found between the Caffeine Use Disorder Questionnaire and Pittsburgh Sleep Quality Index scores. In the generalized linear model analysis, setting the Caffeine Use Disorder Questionnaire score as the dependent variable, statistically significant contributions were observed for gender (women), daily total caffeine intake, and Maslach-depersonalization score variables (p = 0.012, p < 0.001, 0.035, respectively). Conclusions Higher levels of caffeine use disorder have been observed among women, smokers, and individuals with increased caffeine intake. Notably, an increase in professional depersonalization is associated with a rise in caffeine use disorder. Studying physicians' professional depersonalization could aid in addressing caffeine use disorders. Additionally, exploring the caffeine consumption patterns of healthcare professionals displaying depersonalization towards patients' needs is also worthwhile.